The Strategic Planning of Developing Bandung Store in Singapore - Francisca, Christina; Lantu, Donald Crestofel (Journal of Business and Management, 2014)
As one of the great contributor of Indonesia’s national economy, development of Small and Medium Enterprises (SMEs) is still not fully matured. The development of SMEs should apply not only in local area, but also enable them to enter and compete in a more global market. This is how the idea of creating Bandung Store come about. The main theme of this research is international business strategy and focuses particularly on Singapore. The objective of this research is to analyze whether Singapore is an ideal place for starting up Bandung Store and creating developing strategy for the store. In this research, PESTEL and Porter’s Five Forces analysis are used to decide Singapore favorability as destination of Bandung Store, while SWOT analysis and marketing mix are used in creating developing strategy for Bandung Store in Singapore. The data used in this research is gathered from secondary data, in-depth interview, and observation. Keywords: SME, international business, business strategy, marketing mix, SWOT analysis, PESTEL, Porter’s Five Forces